Compromiso laboral y desempeño profesional en docentes universitarios del área de estudios generales en universidades privadas de Perú - Rosales Trabuco, José Eduardo (2022)
Teachers are the neuralgic part of a university. Feeling committed to their work (engagement) leads to a noticeable improvement in the Institution’s work environment and their professional performance. It is in this scenario that it becomes preponderant to evaluate the role of the university teacher and his professional performance based on the commitment he has and what motivates him to be a teacher. Hence, the objective is to determine the relationship between the work commitment variable (engagement) and the professional performance variable in university teachers in the general studies of a private university in Peru. For which an investigation was conducted from the quantitative approach under a non-experimental design at a cross-sectional, descriptive-correlational level, with a population made up of 106 teachers. An adaptation of the UWES Engagement Questionnaire (Utrecht Work Engagement Survey) is used to measure the MINE-DU Professional Teaching Performance variable (Marco del Buen Desempeño Docente). The results of the research indicate that there is statistical evidence of the highly significant relationship between work commitment and professional performance in university teachers in the area of general studies at a private university in Peru in 2018 (0.000 = 0.05)